Interpreting vision: a survey of patristic reception of the Transfiguration and its earliest depiction, with special reference to the Gospel of Luke - Anthony, P; Peter Anthony (2014)
This thesis shows that patristic interpretation of the Transfiguration had a sensitivity to visionary and ecstatic motifs within the synoptic Transfiguration narratives, and particularly Luke’s, which prompted a rich breadth of hermeneutic interaction with our texts. I offer the evidence of my survey of the reception history of the Transfiguration in the first 900 years of Christian history as a way of filling a number of gaps in knowledge in modern biblical scholarship concerning the Transfiguration narratives. This thesis begins, in Chapters 1, 2, and 3, with an appraisal of interpretation offered by modern biblical scholars, patrologists, and art historians. Critical comment often overlooks a series of ambiguities in the narratives, particularly the distinct characteristics of Luke’s version. These include the question of whether the disciples enter the overshadowing cloud, the presence of priestly or cultic imagery, visionary motifs frequently found in apocalyptic texts, such as the disciples’ drowsiness, and Peter’s confusion at not knowing what he said. Chapters 4-7 examine the earliest reception in 2 Peter, the Apocalypse of Peter, and the Acts of Peter, explore at some length Origen’s and Tertullian’s interpretation, and also look at Latin and Greek comment after Origen. I show many ancient writers to understand the disciples as experiencing ecstatic vision. Some also use cultic language appertaining to the Jerusalem Temple in their exegesis of the Transfiguration. They also employ the narrative to interpret other prophetic or visionary texts. Many of these distinguishing features of interpretation frequently stem from their attentiveness to the Lucan narrative. Chapter 8 examines the earliest artistic depictions of the Transfiguration from the sixth century onwards. This chapter indicates that many of the visionary and cultic themes we have outlined in previous chapters are frequently overlooked by art historians, and also that Luke’s narrative exercised a greater influence on representation of the Transfiguration than many people have imagined. This thesis concludes with a reconsideration of the visionary character of the Transfiguration narratives. Many of the ambiguities, overlooked details, and distinctive traits we pointed to in our opening chapters will be seen to have had much greater significance through many centuries of early hermeneutic tradition and artistic depiction than is the case in modern historical critical scholarship.